2019
DOI: 10.1177/1756284819867848
|View full text |Cite
|
Sign up to set email alerts
|

Functional rare variants influence the clinical response to anti-TNF therapy in Crohn’s disease

Abstract: Background: The effect of low-frequency functional variation on anti-tumor necrosis factor alpha (TNF) response in Crohn’s disease (CD) patients remains unexplored. The objective of this study was to investigate the impact of functional rare variants in clinical response to anti-TNF therapy in CD. Methods: CD anti-TNF naïve patients starting anti-TNF treatment due to active disease [Crohn’s Disease Activity Index (CDAI > 150)] were included. The whole genome was sequenced using the Illumina Hiseq4000 platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Studies have revealed that rare pharmacogenetic variants are strongly enriched in mutations predicted to cause functional alterations, and they significantly contribute to the inter-individual variability in drug response. For example, rare genetic variants have been found to influence the clinical response to anti-TNF therapy, with low-frequency loss-of-function variants being associated with the therapy's response [70] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that rare pharmacogenetic variants are strongly enriched in mutations predicted to cause functional alterations, and they significantly contribute to the inter-individual variability in drug response. For example, rare genetic variants have been found to influence the clinical response to anti-TNF therapy, with low-frequency loss-of-function variants being associated with the therapy's response [70] .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in our setting sequenced the entire genome of 41 patients with CD without previous anti-TNF treatment in search of variants related to response to treatment. Two homozygous mutations were identified in HLA-B (variant rs41563412) and HLA-DRB1 (variant rs1071752) associated with non-response and remission, respectively, at week 14 27 .…”
Section: Prediction Of Secondary Loss Of Response To Anti-tnf Based On Hlamentioning
confidence: 99%
“…However, only 30% of the patients achieve this therapeutic objective [16]. Furthermore, the medical community does not have criteria for selecting beneficial drugs for specific patients [17]. Following the failure of medical treatments, patients often resort to surgery, which can lead to both physical and social burdens.…”
Section: Introductionmentioning
confidence: 99%